Application of a Manipulative Media-Assisted Group Investigation Model to Improve Collaboration Among Students at Keleyan 1 Public Elementary School - Oktavia, Fara Medinna; Siswoyo, Andika Adinanda; Stantika, Vero; Azzahroh, Sayyidati Beta Masbaha (Educare : Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This classroom action research aims to improve fifth-grade students’ conceptual understanding of spatial figures and collaboration skills at Keleyan 1 Public Elementary School by implementing the Group Investigation model assisted by manipulative media. The research addresses two key problems: students’ low comprehension of abstract geometric concepts and limited participation in collaborative group activities. The study was conducted using Kurt Lewin’s action research model, carried out over two cycles involving 35 students and a classroom teacher. The instruments used were collaboration observation sheets and conceptual understanding tests. Data were analyzed using descriptive statistics, including percentage comparisons and gain score analysis. Prior to the intervention, 88.6% of students had not met the Minimum Competency Criteria, and only 11.4% showed a high level of collaboration. After two cycles of intervention, students demonstrating high collaboration increased to 40%, and those with low collaboration decreased to 17.1%. Additionally, the average gain score for conceptual understanding reached 0.60, which falls under the moderate improvement category. The findings indicate that the Group Investigation model, when integrated with role assignment, structured collaboration, and the use of concrete, manipulative media, can effectively enhance both cognitive and social dimensions of mathematics learning. This approach provides a promising strategy for fostering active learning in elementary education.